An analog of the Men’shov – Trokhimchuk theorem for monogenic functions in a three-dimensional commutative algebra - Tkachuk, M. V.; Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.54 The aim of this work is to weaken the conditions of monogeneity for functions that take values in a given three-dimensional commutative algebra over the field of complex numbers. The monogeneity of the function is understood as a combination of its continuity and the existence of the Gateaux derivative.